Comparative Study of Genome Divergence in Salmonids with Various Rates of Genetic Isolation - Elena A. Shubina; Mikhail A. Nikitin; Ekaterina V. Ponomareva; Denis V. Goryunov; Oleg F. Gritsenko (International Journal of Genomics)
The aim of the study is a comparative investigation of changes that certain genome parts undergo during speciation. The research was focused on divergence of coding and noncoding sequences in different groups of salmonid fishes of the Salmonidae (Salmo, Parasalmo, Oncorhynchus, and Salvelinus genera) and the Coregonidae families under different levels of reproductive isolation. Two basic approaches were used: (1) PCR-RAPD with a 20–22 nt primer design with subsequent cloning and sequencing of the products and (2) a modified endonuclease restriction analysis. The restriction fragments were shown with sequencing to represent satellite DNA. Effects of speciation are found in repetitive sequences. The revelation of expressed sequences in the majority of the employed anonymous loci allows for assuming the adaptive selection during allopatric speciation in isolated char forms.